UZBEK-FRENCH RELATIONS AS A BINDING PART OF INTERNATIONAL CULTURAL AND HISTORICAL EXPERIENCE - Davronova, Zulfiya (Ижтимоий-гуманитар фанларнинг долзарб муаммолари / Актуальные проблемы социально-гуманитарных наук / Actual Problems of Humanities and Social Sciences., 2024)
This article deals with the problems of discussing the attempts undertaken in the Republic on developing the process of Uzbekistan-France relations and cooperation in intercultural context on the basis of the ancient sources in the condition of international globalization. It also contains information about the process of learning those sources and discuss the history of the cooperation between Uzbekistan and France on creating cultural and en lightenmental possibilities and political and legal basis.